Bastards in the Belgian Manuscript. (19th December 2013) - Emerson, Catherine
While modern Belgians proudly identify with the figure of the bastard, nineteenth-century nationalists saw the fifteenth-century Valois Burgundian 'state' as the origin of their country. Coincidentally, this was a period and a region where bastards had risen to political and social prominence. This article examines one cultural trace of this; the use of an abbreviation for the word bastard in manuscripts written in French in Valois Burgundy. Used by men and women for whom bastard was a title, the abbreviation does not reflect any desire to conceal a taboo word, but rather is a response to the frequency of occurrences of bastards. Abbreviation is also found in French manuscripts where the word occurs frequently, but it is not the same standardized abbreviation used in Valois Burgundy. This one abbreviation points to a divergence in material culture in the two regions.